Temperature effect on forming of self- reinforced polypropylene based lightweight metal composite structure - Dhar Malingam, Sivakumar; Kalyanasundaram, Shankar (Penerbit Universiti Teknikal Malaysia Melaka, 2013)
This study investigates the effects of blank temperature on the strain of self-reinforced polypropylene based lightweigh Metal Composite Structure(MCS). Comparisons between MCS and monolithic aluminium revealed that MCS shows a more uniform strain distribution over the punch face of the laminate and reduction in the required work to form stamping operation. Moreover MCS gives a 30% weight reduction compared to monolithic aluminium. The experimental results obtained in the present study shows MCS systems have the potential to be adapted to high volume production technique of stamp forming. A significant finding from this work is that these material systems exhibit forming characteristics that are comparable and sometimes superior to metal forming.